Ekspresi VEGF Sel Adenokarsinoma Mamma Pada Pemberian Oral Ekstrak Andrographis paniculata - NUGRAHANINGSIH NUGRAHANINGSIH; SARJADI SARJADI; EDI DHARMANA; HERTANTO WAHYU SUBAGIO (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
Angiogenesis was needed to fulfill nutrition and oxygen demand for tumor growthh and its metastase. Vascular endothelial growth factor (VEGF) was a potential proangiogenic factor of angiogenesis process. In vitro study of Andrographis paniculata extract showed decreasing tend of VEGF level serum on PC-3 cancer cell line. The aim of this study was to prove the effect of oral administered Andrographis paniculata extract on VEGF expression of adenocarcinoma mammae C3H mice. Twenty four mice was transplanted with adenocarcinoma mammae randomly to four groups. Andrographis paniculata extract at dose 5, 10, and 15 mg/day were given on mice group along 14 days. One group another as a control. VEGF expression were examined use immunohistochemistry staining. Anova test showed difference VEGF expression among reseach groups (p=0,000, r=-0,953). The highest of VEGF expression index 24,8 was found on control group, and the lowest 19,4 was found on group which received 15 mg/day. We concluded that oral administration of Andrographis paniculata extract decreased VEGF expression of adenocarcinoma mamme C3H mice.